1, 3, 4, 6-Tetrachloroglycoluril (TCGV) mediated isothiocyanation of phosphites, phosphonites and phosphinites. (11th November 2022) - Guo, Huichuang; Li, Junchen; Zhang, Yulong; Mao, Tengfei; Gao, Runli; Guo, Yongbiao; Shi, Enxue
Abstract: A universal and facile isothiocyanation protocol of P(O)H functionality with inorganic thiocyanides mediated by 30% equimolar 1, 3, 4, 6-tetrachloroglycoluril (TCGV) was developed for the preparation of the corresponding phosphoroisothiocyanates, phosphonoisothiocyanates and phosphinoisothiocyanates. P(O)Cl was found to be the intermediate in situ formed in the reaction. Graphical Abstract: UF0001